Pengaruh Perbedaan Tipe Pemangkasan Terhadap Pertumbuhan Dan Hasil Tanaman Mentimun (Cucumis sativus L.) VARIETAS METAVY F1 - Ahmad Sofyan Maulana; Darso Sugiono; Devie Rienzani Supriadi (Peneliti.net, 2023)
The purpose of this research is to get the best pruning for cucumber (Cucumis sativus L.) Var. Metavy F1. The research was conducted at Pasirkamuning Village, Karawang District from February to April 2022. The research method used is an experimental with group randomized block design (RED) with 6 treatments, there are A (without pruning), B (without pruning on the shoot of the main steam + pruning all the lateral branches), C (without pruning on the shoot of the main steam + pruning on 3 lateral branches), D (without pruning on the shoot of the main steam + pruning on 5 lateral branches), E (pruning on the shoot of the main steam + 3 lateral branches), F (pruning on the shoot of the main steam + 5 lateral branches). In this experiment 6 treatments were repeated 4 time so that there were 24 plots in total. The result of this experiment found that the differentiation of pruning on the main steam and lateral branch hasn't a significant effect on the growth and production of melon (Cucumis sativus L.) Var. Metavy F1.